The Interplay of Planning and Decision-Making in Organizational Management: A Literature Reviews - Elmanisar, Velnika; Hadiyanto, Hadiyanto; Irsyad, Irsyad (Postgraduate School, Universitas Negeri Padang, 2024)
This literature reviews aims to explore the interconnected roles of planning and decision-making in organizational management. The study synthesizes insights from existing research to explore how structured planning and informed decision-making processes contribute to sustainable growth. Findings reveal that decision-making is a core leadership function, involving rational and logical steps such as problem identification, alternative generation, solution selection, and implementation. Effective decision-making balances logic with intuition, enabling leaders to address challenges of varying complexity. Similarly, planning emerges as a fundamental process for goal-setting and resource allocation, supporting decision-making through clear strategies and structured implementation. Types of decision-making, including importance-based, regularity-based, and environment-based decisions, underscore the need for flexibility and adaptability in diverse scenarios. Factors such as organizational hierarchy, problem complexity, situational context, and resource availability further influence these processes. By integrating robust planning and decision-making practices, organizations can enhance their capacity for innovation, maintain strategic alignment, and achieve resilience in dynamic environments.